EFEKTIVITAS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KEKERASAN SEKSUAL DALAM PERSPEKTIF UNDANG-UNDANG TINDAK PIDANA KEKERASAN SEKSUAL - Amri, Qoonitah; Sambas, Nandang (LPPM STIH Awang Long, 2025)
Article 1 paragraph (3) of the 1945 Constitution emphasizes that the State of Indonesia is a State of Law. Regulations begin in every aspect of the life of the Unitary State of the Republic of Indonesia, according to these rules. The lives of people all over the world are influenced by very important rules. Law enforcement is the only place where regulations can be implemented naturally and effectively. From various information in the news media, issues related to sexual violence continue to be a hot topic of discussion. The increase in cases of sexual violence in various levels of society has led to more and more reports regarding this problem. However, in practice, we often find that many children become victims of unethical behavior carried out by men. The formulation of the problem that will be discussed is 1. What is the legal protection for victims of sexual harassment committed by Herry Wirawan, 2. What is the criminal responsibility for cases of sexual harassment committed by Herry Wirawan. This research uses normative juridical legal research. Soerjono Soekanto defines the normative juridical approach as a legal research method that focuses on library materials or secondary data. The increasing number of violent crimes is a serious concern for the government. The community also shows a deep sense of anger towards the high rate of violence that often occurs in various aspects of life in Indonesia.